مقارنة الأديان عند ابن المجد البعلي في كتابه "الظل الممدود في الذب عن نبي الله داود": دراسة تحليلية - حسين، عمرو محمد أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research examines the work of Al-B'ali, Muhammad ibn al-Majd ( 768 AD), namely: Al-Zill al-Mamdud fi al-Dhabb 'an Nabiy Allah Dawud (The Stretched Shadow in Defending God's Prophet David). The study looks into the methodology of Ibn al-Majd's analysis and its relevance to contemporary setting. The issue studied by Ibn al-Majd is the story attributed to David (peace be upon him), Uriah the Hittite and Bathsheba. Using analytical and inductive methodology, the study begins by looking into Ibn al-Majd's biography and creatively presents it in a unique form. The researcher studies the manuscript and extracts the methodology adopted by Ibn al-Majd. A study is also made on the methodology of his scientific school of al-Hadith- in studying religions. The researcher seeks to set the methodological features of this school, and highlights its characteristics as an important field to be explored through scientific research. The researcher also reviews the content of the book by critically analyzing Ibn al-Majd's creative solutions that he had provided. One of the remarkable features of Ibn al-Majd is that his analysis is very much in tune with contemporary reality.